The Performance Contexts of Trochaic Tetrameters Catalectic - Bowie, Ewen (Classica - Revista Brasileira de Estudos Clássicos, 2018)
The paper explores the evidence for the archaic performance context or contexts of Archilochus’ and Solon’s trochaic tetrameter catalectic poems, noting that they were chanted rather than sung or spoken and thus different from both elegy and iambic trimeters. It argues that in Archilochus’ fragments apparently lengthy battle-narratives, concern with the polis as a whole, and addresses to elite individuals point to their first audience being a formal gathering of warrior-citizens, perhaps before a battle, or perhaps at a mass cremation following a battle such as that attested by the late-eighth-century polyandrion in Paroikia. It is suggested that Solon’s very political tetrameters may also have been addressed to a formal citizen assembly, with possible reperformance at the Apatouria.